Key success factors for quality management implementation - Pimentel, L.; Major, M. (17th QMOD−ICQSS Proceedings, 2014)
Purpose: This paper aims to identify the crucial factors that induce successfully a quality management process implementation. Particularly, it intends to examine how total quality management (TQM) can be fully achieved by implementing in organisations specific items, frameworks or factors, duly integrated into a procedural sequence. Methodology/Approach: The paper adopts an explanatory longitudinal case study, using a multiple-case research design (Yin, 2009) to support the investigation. The study deals with the implementation of a quality management programme (QMP), linked to organizational change and delivering excellence, in several Government agencies supervised by a specific Ministry in Portugal. The case study comprises three different field sites where the results and outcomes of the QMP implementation were differently observed. The QMP was basically translated into TQM (encompassing the common assessment framework - CAF, ISOs, or quality manuals). Collection of evidence comprised the conduct of 64 interviews (in three phases, between January 2010 and May 2014), and data and written documentation analysis. The study was built on quality management literature, highlighting the contributions of Oakland (2004, 2011) and Oakland and Marosszeky (2006). Findings: The QMP implementation in the field sites showed different levels in outcomes and results. It was also found that the main items to deliver excellence, identified in the ‘Oakland TQM model’ (the 4 Ps and the 4 Cs), explain mostly the different perceptions of results and outcomes. Other items/factors were identified that can explain those differences, concretely power and collective involvement. Research implications: Borrowing from the ‘Oakland TQM model’, the paper enriches the literature on quality management by confirming the Oakland items as key factors to explain the achievement of quality management and TQM, particularly in organisations. The investigation also identified other factors that can help to explain the successful quality management implementation, namely power and collective involvement. Consequently, a refined ‘Oakland TQM model’ (Keating, 1995; Vaivio, 2007) is proposed, and a visualization of the interaction of the items/factors in an input-output perspective. These implications are important for academics and practitioners. Originality/Value of the paper: This study helps to synthesize the key factors to successful implementation of quality management in organisations and to frame and link those factors to existing literature. Particularly, the success factors identified in the case study imply the proposal of a refined ‘Oakland TQM model’. Furthermore, the model is translated into an input-output interaction of those factors, representing the practical implementation process that was found in the study. Moreover, the paper analyses the implementation of quality management in three government agencies, constituting three field sites subject to the same environmental pressures. These field sites support a longitudinal comparative and explanatory case study, which has received so far little attention from literature on quality management. Key-words: Quality management; Total quality management; Quality management models; Explanatory case study